The Effect of Subjective Norms, Perceived Behavior Control, Price, Service Quality, Airline Safety, Airline Reputation on Behavior Intention in Shaping Buying Behavior of LCC Super Air Jet Passengers in Surabaya - Gerald Yeremi Ruddy Ngongoloy; Oliandes Sondakh (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
The purpose of this study is to examine how the Subjective Norm, Perceived Behavior Control, Price, Service Quality, Airline Safety, and Airline Reputation factors of Super Air Jet passengers affect Behavior Intention which ultimately shapes the Buying Behavior of passengers of this low-cost airline. A survey of 200 passengers was conducted to test the hypothesis. Data processing was carried out using SmartPLS 3 software. The results show the important role of Subjective Norm and Airline Safety in the Behavior Intention and Buying Behavior of Super Air Jet LCC passengers.